Factors related to Oral Health Care of Diabetic Patients in Wat Sriwareenoi Health Promoting Hospital, Sisa Chorakhe Yai Sub-district, Bang Sao Thong District, Samutprakan Province - Katanyutanon, Tuangporn; Jongcharoen, Wannarat; Phanchan, Suwimon; Jantamontree, Phatchara; Eknum, Phensiri; Siriwat, Oraphan; Raktham, Pongsit; Sengla, Wacharadon (Journal of Health Science of Thailand, 2019)
The objectives of this cross-sectional descriptive research were to study the oral health care and the relationship between perception factors, modifying factors and induction factors influencing the oral health care of diabetic patients in Wat Sriwareenoi Health Promoting Hospital, Sisa Chorakhe Yai Sub-district, Bang Sao Thong District, Samutprakan Province. The sample of 125 diabetic patients were selected through stratified random sampling based on gender. Data were obtained by using questionnaire and analyzed them by frequency, percentage, mean, standard deviation, fisher’s exact test, and Spearman’s rank correlation analysis. It was found that the oral health care practice of diabetic patients were at the moderate level. The oral cleaning, oral check-up and avoiding food items which caused negative influences on oral cavity were at moderate level. However, the behavioral practices to avoid dental health risk were at the high level. The modifying factors including gender, age, income, educational attainment, marital status, and knowledge on the oral health care did not significantly associate with the oral health care behaviors of diabetic patients. Moreover, the perception factors such as perceived susceptibility of oral diseases, perceived severity and complications in the oral cavity, perceived benefits of oral health care, perceived barriers in oral health care had significantly positive relationship with the care (r=0.32, 0.23, 0.35, 0.31, and p<0.01). The induction factors such as accepting the information about oral health care had positive relatonship with the oral health care of the patients (r=0.34, p<0.00). This research suggests that oral health care should be promoted in diabetic patients by providing information about oral health care that support the patients to perceive susceptibility of oral diseases, severity and complications in the oral cavity, benefits of oral health care, and barriers of oral health practice.